2017
DOI: 10.1007/s11548-016-1514-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of acetabular orientation and femoral anteversion using images of three-dimensional reconstructed bone models

Abstract: The differences between the two measurements are explained by the use of different tools. However, more consistent measurements were possible using the images of 3D reconstructed bone models. Therefore, 3D measurement can be a good alternative to measurement using 2D slice images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…This difference had been found previously by Hartel et al [10]. The mean values of FNV in Asians of the present study are close to those found by Zhang and Park who studied a Chinese population (16.4° and 17.3°, respectively) [23,38]. The TT was also significantly lower in Asian subjects with a mean difference of 2.8° [8,12,31,32].…”
Section: Discussionsupporting
confidence: 91%
“…This difference had been found previously by Hartel et al [10]. The mean values of FNV in Asians of the present study are close to those found by Zhang and Park who studied a Chinese population (16.4° and 17.3°, respectively) [23,38]. The TT was also significantly lower in Asian subjects with a mean difference of 2.8° [8,12,31,32].…”
Section: Discussionsupporting
confidence: 91%
“…Nowadays, the two-dimensional (2D) tomography images could be converted into the three-dimensional (3D) models using specialized imaging programs. 3D modelling, which have an increasing interest in the literature, that could help the surgeons to better understand the lesions by visualizing the real anatomical features compared to plain radiographs and 2D tomography images [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Implant modifications and optimizations, which are made in accordance with genderspecific anatomical differences, could increase the postoperative functional results [7]. The effects of gender, age and race on anatomical features using the tomographic measurements, were largely investigated in the literature [1,3,4,[8][9][10]. In some of these studies, the femoral markings and measurements were performed using 2D methods [3,4], while in a limited number of studies all the femoral markings and measurements 1 were performed on 3D models [1,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, measurements taken in two-dimensional (2D) axial planes have proven less consistent. 21 On the other hand, measurements taken on three-dimensional (3D) CT images could be a gold standard for obtaining reliable measurements of the femoral component regardless of patient positioning. 22 …”
Section: Introductionmentioning
confidence: 99%